Testes Proteases Expression and Hybrid Male Sterility Between Subspecies of Drosophila pseudoobscura - Alhazmi, Doaa (G3 (Bethesda), 2019)
Hybrid male sterility (HMS) is a form of postmating postzygotic isolation among closely related species that can act as an effective barrier to gene flow. The Dobzhansky-Muller model provides a framework to explain how gene interactions can cause HMS between species. Genomics highlights the preponderance of non-coding DNA targets that could be involved in gene interactions resulting in gene expression changes and the establishment of isolating barriers. However, we have limited knowledge of changes in gene expression associated with HMS, gene interacting partners linked to HMS, and whether substitutions in DNA regulatory regions (cis) causes misexpression (i.e., expression of genes beyond levels found in parental species) of HMS genes in sterile hybrids. A previous transcriptome survey in a pair of D. pseudoobscura species found male reproductive tract (MRT) proteases as the largest class of genes misregulated in sterile hybrids. Here we assay gene expression in backcross (BC) and introgression (IG) progeny, along with site of expression within the MRT, to identify misexpression of proteases that might directly contribute to HMS. We find limited evidence of an accumulation of cis-regulatory changes upstream of such candidate HMS genes. The expression of four genes was differentially modulated by alleles of the previously characterized HMS gene Ovd.